2006
DOI: 10.1007/s00701-006-0771-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric analysis of cerebral substrates and nitric oxide delivery in cerebrospinal fluid in patients with intracerebral haemorrhage: correlation with hemodynamics and outcome

Abstract: This study confirms the correlation between the level of EAAs and the outcome of ICHs, suggesting that neurochemical monitoring of these substances may have a role in caring for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
12
0
3
Order By: Relevance
“…The glutamate content has been found to be clearly elevated in perihematomal brain tissue, and the prognosis of ICH is closely related with the EAA level [4,17,18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The glutamate content has been found to be clearly elevated in perihematomal brain tissue, and the prognosis of ICH is closely related with the EAA level [4,17,18].…”
Section: Discussionmentioning
confidence: 98%
“…Cerebral damage as a consequence of glutamate-mediated excitotoxicity is a major consequence of stroke. Recently published data confirmed the correlation between the level of excitatory amino acids (EAAs) and the outcome of ICHs, suggesting that neurochemical monitoring of these substances may have a role in the care of patients [4]. Glutamate-related excitotoxicity may have an important impact on secondary injury [1].…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies indicated that ICH increased the level of glutamate in the perihematomal area starting from 30 min, with a peak at 6 h to 12 h (Qureshi et al, 2003a, Nilsson et al, 2006). There was a 25-fold increase in the CSF glutamate level in ICH patients (Chiang et al, 2006). Glutamate induces the activation of the NMDA receptor (NMDAR) and leads to the formation of a complex of NMDAR-PSD95-nNOS.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that intracerebral hemorrhage (ICH) increases the level of glutamate in the perihematomal area and in cerebral spinal fluid (CSF) during the acute phase of ICH (Chiang et al, 2006, Nilsson et al, 2006). In addition, blood and CSF glutamate concentrations independently predict a poor clinical outcome in ICH patients (Castillo et al, 2002, Chiang et al, 2006); however, whether elevated glutamate activates neuronal nitric oxide synthase (nNOS) in the ICH brain and whether nNOS is an important target for ICH treatment have not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation